The Impact of Junk Food on Adolescent Health: Strategies to Promote Healthy Eating in Educational Environments - Nadila, Putri; Tambunan, Torang Jhon Raido; Ingtiyas, Fatma Tresno; Ginting, Laurenna (Journal Corner of Education, Linguistics, and Literature, 2024)
Consuming food is a daily necessity needed to meet nutritional requirements that function to fulfill the basic needs of humans. Adolescents generally love fast food because it comes in a wide variety and is very easy to obtain. This has become a concern in the educational environment to promote healthy food within educational settings such as schools. The purpose of this article is to examine the impact of fast food consumed over the long term on the health of adolescents. Fast food consumed over a long period can cause the accumulation of addictive substances and lead to health issues such as diabetes and obesity. The method used in this research is the literature review method. The literature study was conducted systematically following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analysis) guidelines, with publication years from 2019-2024. A total of 20 journals were obtained using the keywords: 'Adolescents dangerous diseases, Fast food, junk food'. Out of the 20 journals reviewed, only 15 journals showed relevant results, indicating that fast food has an impact on the occurrence of diabetes mellitus and obesity in adolescents. This is due to the high sugar and fat content in fast food.